From managing madness to managing well-being the history of the Philippine Mental Health Association Baguio-Benguet Chapter (1959-1973) - Imbat, Vincent Honrado (2013)
This is an institutional history of the Philippine Mental Health Association Baguio- Benguet Chapter Incorporated (PMHA-BBCI) FROM 1959 TO 1973. It is also an investigative pursuit of the framework and technologies that the institution employed in addressing the social problem of mental illness throughout Baguio's past. This study traces the beginnings of the Philippine Mental Health Association(PMHA) from the development of the disciplines of psychiatry, neurology and psychology during the American period. It chronicles the establishment of PMHA Baguio Benguet Chapte in 1959 as part of the decentralization and regionalization of psychiatric services by the government and the medical community after the second world war. The study also discusses the functions, operations and activities of the chapter as guided by its community-based framework of mental health care. This study illustrate the ability of community-based psychiatry to transfer power from the hegemonic insane asylum like the National Mental Hospital (NMH) to the regional centers of the PMHA strengthening the authority bestowed upon physicians and social workers on the labeling of certain behaviors as abnormal and prescribing norms for the management of the well-being of citizens of the state -- Author's abstract.
Thesis (Bachelor of Arts in Social Sciences)--University of the Philippines Baguio, 2013.
Includes bibliographical references (leaves 140-144).
Keywords: Philippine Mental Health Association Baguio-Benguet Chapter; Mental health services -- Philippines